Suppression of Neutrophil Antimicrobial Functions by Total Particulate Matter From Cigarette Smoke - Zhang, Yao; Geng, Shuo; Prasad, G. L.; Li, Liwu (Frontiers in Immunology, 2018)
Chronic cigarette smoking is widely known to alter immune functions and compromise hose defense against microbial infection. Neutrophils play an essential role in the immune defense against microbial pathogens and also participate in the development of the inflammatory responses. However, there is limited information about the effects of cigarette smoking on neutrophil response. In this study, cultured bone marrow neutrophils were exposed to total particulate matter (TPM) from cigarette smoke. We found that TPM not only reduced LPS-induced TNFα production, but also suppressed neutrophil bactericidal activity. We also observed that TPM priming reduced the expression of NADPH oxidase component gp91 and iNOS, molecules important for bacterial killing. Mechanistically, we documented that TPM-primed neutrophils have reduced STAT1 activation following subsequent LPS challenge. STAT1 is a key transcription factor responsible for the expression of inflammatory genes as well as gp91 and iNOS. Collectively, reduced STAT1 activation and reduced NADPH oxidase/iNOS may potentially explain the compromised anti-microbial function of TPM-programmed neutrophils. Taken together, our findings reveal that the key innate immune neutrophil is subject to reprogramming by smoking to adopt an immune-suppressed state, potentially responsible for chronic smoking-mediated immunosuppression.